Piloting private spare parts supply shops for Afridev handpump in Amhara to scale-up in country and beyond - A. Desalegne Mihretie (2009)
To achieve MDG and UAP targets, the WSSDP of Ethiopia has adopted a number of technologies for rural areas, among which the greatest majority is sinking hand dug wells. As a result, several Afridev hand pumps are installed each year. This will continue in a large scale in the coming 4 years and beyond. To serve sustainably, fast and slow wearing parts of this pump need to be replaced timely and when broken respectively. However, so far, spare parts supply chain for the pump was not established. Hence, a large number of this pump is functioning without regular preventive maintenance and some are already dysfunctional. The later will hamper both MDG & UAP targets for water supply. Therefore, it is timely for the actors in the sector to support the private sector in piloting spare parts supply shops. The lessons learned would facilitate scaling–up and the development of WatSan centers in country and elsewhere.